Application of myoelectric elbow flexion assist orthosis in adult traumatic brachial plexus injury: a retrospective clinical study. Issue 6 (11th December 2021) - Pulos, Nicholas; van den Berg, Catherine; Kaufman, Kenton R.; Shin, Alexander Y.
Abstract : Background: Adult traumatic brachial plexus injuries (BPIs) can result in severe impairment following penetrating wounds, falls, and motor vehicle accidents or other high-energy trauma. Objective: Quantify functional outcomes of adult patients with a BPI using a myoelectric orthosis to restore elbow flexion. Study design: Retrospective review. Methods: A clinic specializing in the BPI treatment at a large academic medical center tested nineteen adult patients with BPI. These patients had failed to achieve antigravity elbow flexion following their injury and observation or surgical reconstruction. They were provided a myoelectric elbow orthosis (MEO) if they had detectable electromyography signals. Results: There was significant improvement in strength and significant reductions in function and pain when using an MEO. Following initiation of the MEO, 12 of the 19 patients had clinical improvements in muscle strength, 15 patients showed improvement in their DASH, and 13 patients reported improvements in their Visual Analog Scale. Conclusion: The use of an MEO improves elbow flexion strength, increases function, and reduces pain in the majority of patients with BPI and inadequate elbow flexion following observation or surgical reconstruction.